Rachel: An IoT smart plant based on FIWARE - Baca Gómez, Yolanda Raquel; Estrada Esquivel, Hugo; Martínez Rebollar, Alicia; Vásquez, Daniel Villanueva (International Journal of Scientific Research and Management (IJSRM), 2019)
The Internet of Things (IoT) allows objects becoming producers and users of information generated by themselves, by people or by other systems and also facilitates automating applications. One of the IoT topics is home automation, which allows monitoring and manipulating objects in a house. Because of the growing of IoT, there are emerging different platforms to face this technology, such as FIWARE, which provides components and data models that facilitate the development of IoT applications. In this paper, a smart plant prototype based on FIWARE is presented. The plant environment data is gathered through different sensors, and is sent to a FIWARE component called Orion Context Broker (OCB) in a FIWARE data model structure. The OCB allows to manage and publish the data, so that, the data is available in the cloud ready to be consumed by other users or applications and to automate applications.